2002
DOI: 10.1124/mol.62.2.304
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ceramide Metabolism on P-Glycoprotein Function in Immature Acute Myeloid Leukemia KG1a Cells

Abstract: Previous studies have emphasized the role of glucosylceramide (Glu-Cer) synthase in multidrug resistance (MDR) regulation. However, the mechanism by which the inhibition of this enzyme results in increased drug retention and cytotoxicity remains unclear. In this study, we investigated the respective role of ceramide (Cer) accumulation and Glu-Cer derivatives depletion in MDR reversal effect of 1-phenyl-2-decanoylamino-3-morpholino-1-propanolol (PDMP), a Glu-Cer synthase inhibitor. We show here that treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 37 publications
0
20
1
Order By: Relevance
“…Our results are in contrast with those of Plo et al (23), who show modulation of Pgp activity by the gangliosides GD 3 and GM 3 in acute myeloid leukemia cells. In their study, they used only PDMP to reduce ganglioside content and showed that an z50% reduction is sufficient to exert an effect on Pgp activity, whereas in our study, a stronger reduction of ganglioside content by either of two different GCS inhibitors was without effect.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…Our results are in contrast with those of Plo et al (23), who show modulation of Pgp activity by the gangliosides GD 3 and GM 3 in acute myeloid leukemia cells. In their study, they used only PDMP to reduce ganglioside content and showed that an z50% reduction is sufficient to exert an effect on Pgp activity, whereas in our study, a stronger reduction of ganglioside content by either of two different GCS inhibitors was without effect.…”
Section: Discussioncontrasting
confidence: 56%
“…In their study, they used only PDMP to reduce ganglioside content and showed that an z50% reduction is sufficient to exert an effect on Pgp activity, whereas in our study, a stronger reduction of ganglioside content by either of two different GCS inhibitors was without effect. The different outcome may be attributable to cell type-dependence or the fact that the myeloid leukemia cells used by Plo et al (23) highly overexpress Pgp as a result of drug selection or transfection with the mdr-1 gene, whereas the human neuroblastoma cell lines used in our study were neither selected nor transfected.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…In GARF cells, the overexpression of Pgp was accompanied by an increased LacCer level. Plo et al have shown that treatment with PDMP results in increased rhodamine 123 retention and potent chemosensitization of Pgp-expressing leukemic cells (27). In the above study, PDMP increased ceramide levels but reduced ganglioside levels.…”
Section: Discussionmentioning
confidence: 53%